Workshop Infografis bagi Guru sebagai Media Pembelajaran Alternatif di SD Laboratorium Percontohan UPI Kampus Serang - Firman Robiansyah; Ima Ni'mah Chudari; Sri Wuryastuti (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The use of effective learning media for students is a non-negotiable need. Especially during the pandemic, the online learning system requires teachers to be creative in preparing interesting and fun teaching materials for students so that the information conveyed in learning can be effectively accepted and understood by students. In today's world of education, infographics can be a new option for teachers in delivering lessons to their students. By using infographics as teaching aids, it is as if we are telling a visual story to our students. This community service in the form of a workshop aimed to help elementary school teachers of the UPI Serang Campus Teaching Laboratory Elementary School in improving their skills in making infographic learning media. It is hoped that the results of this community service is to make Teaching Laboratory Elementary School teachers to be able to make infographic learning media to be an alternative in presenting learning media that support an effective and fun learning process for students.